Recent Advances in the Assessment of Flood Risk in Urban Areas - Ferreira, Tiago Miguel (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The adverse effects of flood disasters in urban areas have been increasing in severity and extent over the past years. The amount of loss resulting from these events is also increasing exponentially, particularly in highly urbanised urban areas, where the effects of intensive land use and climate change are particularly extreme-all despite that our scientific knowledge, technical competence, and computational capacity to develop highly sophisticated and accurate forecasting and simulation models are higher than ever, as is our capacity to map and analyse flood-related data. In order to tackle this global issue, it is fundamental to keep on promoting and developing fundamental and applied research that allows the better targeting of interventions to improve resilience, reduce vulnerability, and enhance recovery as well as assisting decision-makers in delivering more effective flood risk-reduction policies. This book aims to contribute to this goal by providing a space in which to share and discuss recent studies and state-of- the-art methodologies focused on the assessment and mitigation of flood risk in urban areas. It includes nine high-quality chapters authored by eminent scholars who had the tremendous generosity to join me in this editorial project. The range of topics covered by these nine studies is extraordinarily vast, reflecting the complexity of the current challenges associated with the topic.